A mechanism for evasion of CTL immunity by altered O-glycosylation of HLA class I. (17th January 2017) - Sutoh Yoneyama, Mihoko; Tobisawa, Yuki; Hatakeyama, Shingo; Sato, Misaki; Tone, Kiyoshi; Tatara, Yota; Kakizaki, Ikuko; Funyu, Tomihisa; Fukuda, Minoru; Hoshi, Senji; Ohyama, Chikara; Tsuboi, Shigeru
Abstract : Anti-tumour immunity by cytotoxic T-lymphocytes (CTLs) is essential to suppress tumour progression. Cancer cells that evade CTL immunity proliferate in the host, promoting metastasis, but mechanisms underlying this capacity remain unknown. Here we report that bladder cancer cells metastasized to lymph nodes evade CTL immunity by a new mechanism via altered glycosylation. CTLs normally recognize and kill cancer cells presenting antigenic peptides on human leukocyte antigen (HLA) class I. We show bladder cancer cells expressing the O -glycan processing enzyme, core2 β-1, 6- N -acetylglucosaminyltransferase (C2GnT) exhibit HLA class I O -glycan modified with poly- N -acetyllactosamine and are highly susceptible to CTL. In those cells, poly- N -acetyllactosamine on HLA class I O -glycan binds galectin-3 to form a cell-surface molecular lattice, enabling efficient cell-surface retention of HLA class I. In contrast, bladder cancer cells in which C2GnT is downregulated show decreased levels of poly- N -acetyllactosamine on HLA class I O -glycans, attenuating lattice formation and reducing the cell-surface half-life of HLA class I. These tumour cells present antigenic peptides less efficiently, thereby evading CTL lysis and facilitating metastasis.